PEROKOK PASIF SEBAGAI FAKTOR RISIKO PENYAKIT KARDIOVASKULAR DAN KEMATIAN TERKAIT PENYAKIT KARDIOVASKULAR: SYSTEMATIC REVIEW - Pratiwi, Ni Nyoman Sriwulan; Swi Antara, I Made Putra; Adelia Yasmin, A.A. Ayu Dwi; Yudha Dewangga, Made Satria (Universitas Udayana, 2022)
Background: The harmfull effects of smoking are not only applied to active smokers but also secondhand smokers. Reseach show that secondhand smokers have an increased risk of cardiovascular disease and cardiovascular mortality. Hence, this systematic review aims to evaluate further the role of passive smoking as the risk factor for cardiovascular disease and cardiovascular mortality. Methods: This systematic review was conducted based on the new PRISMA guidelines. This review included the relevant cohort prospective studies from the last five years in Pubmed, Science Direct, and Cochrane Library. Results: There were five relevant studies included in this review. Four studies found that passive smoking has a higher risk of cardiovascular disease. One study reported that passive smoking is a risk factor for cardiovascular mortality. Conclusion: Passive smoking is a significant risk factor for both cardiovascular disease and cardiovascular mortality. Keywords: secondhand smoker, passive smoking, cardiovascular disease, cardiovascular mortality